The AI Revolution in Rheumatoid Arthritis: Enhancing Diagnosis, Prognosis, and Personalized Care - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Rheumatoid arthritis RA is a chronic, systemic autoimmune disease characterized by joint inflammation, pain, and progressive joint destruction. Affecting nea...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine